The relationship between gender identity development and career decision-making process among high school learners. - Rammutla, Lara Letlhogonolo (My University, 2010)
According to Erikson (1968), adolescents and young people are greatly engaged in the process of identity development with the intentions to evade a state of diffusion and role confusion. Not much research in the areas of identity formation and career development has explored the possible relationship between these two phenomena. The purpose of this study was to investigate whether there is a relationship between gender identity formation (identity statuses) and career decision-making process among high school learners. In addition the study explored if there are gender differences between males and females on identity statuses, as well as on career decision-making process. A sample of 156 Grade 12 learners participated in the study. The Revised Extended Objective Measure of Ego Identity Status (Bennion & Adams, 1986) and the Study Choice Task Inventory were administered to the learners. Findings of the study showed correlation between the identity statuses of Diffusion, Foreclosure and Moratorium for males and females and the career decision–making process. No statistically significant differences were found between males and females on the variables, namely, identity statuses and aspects of career decision-making processes. Implications for theory and practice and recommendations for future research are provided.
Keywords: Adolescence; Identity statuses; Gender; Decision-making process; Study choice; Decisional task